Metabolic syndrome, obesity and ethnicity—The SAMINOR Study - Michalsen, Vilde Lehne (UiT The Arctic University of Norway, 2021)
Clustering of certain cardiometabolic risk factors is known as metabolic syndrome (MetS). MetS is associated with an unhealthy lifestyle and the prevalence is increasing alongside the obesity epidemic, making it an important public health issue. Both MetS and obesity are common in the adult population in rural Northern Norway, which comprises an ethnically mixed population. MetS is defined using ethnicity-specific cut-offs for waist circumference (WC), but there is much uncertainty with respect to obesity and ethnicity. Using various regression models we analysed data from the SAMINOR Study, comprising SAMINOR 1 (2003–2004) and SAMINOR 2 (2012–2014). We examined the change in prevalence of MetS between these two time points by sex and Sami/non-Sami ethnicity, and estimated the mortality of MetS, obesity-metabolic phenotypes, and continuous obesity measures. Next, we modelled the ethnic-specific relationships between metabolic markers and obesity measures. Finally, we examined the correlation between body mass index (BMI) and height, estimated a sample-specific height-corrected weight index and compared it in Sami and non-Sami. The prevalence of MetS increased over time and was present in more than one third of the population in 2012–2014. The increase differed by sex, but not ethnicity. MetS was associated with a 50% increased cardiovascular disease (CVD) mortality. In men, metabolically healthy obesity was associated with a three-fold increase in CVD mortality compared to metabolically healthy non-obesity. The association was linear and positive for all obesity measures regardless of metabolic health status in men. However, there were only weak associations between metabolically healthy obesity and mortality in women. We found no evidence of ethnic-specific relationships between obesity measures and metabolic markers. Because height differs in Sami and non-Sami, BMI comparisons are biased. Cardiometabolic health is deteriorating in rural Northern Norway. This development is not influenced by ethnicity. Previous ...